Assessment of Soil Fertility of Grape Field at Bijapur District, Karnataka, India - A. S. Pujar; M. S. Yadawe; U. S. Pujeri; K. G. Pujari; S. C. Hiremath (E-Journal of Chemistry)
Assessment of soil fertility at Bijapur district (Karnataka, India), grape yard of various localities was undertaken. Grape is an important fruit crop of northern parts of Karnataka and it is grown over 9000 hectors. The survey includes 15 grape yards and surface soil samples up to depth of 30 cm were collected and after drying were passed through 2 mm sieve. The soil samples were analyzed for various attributes. The data on analysis revealed that the soil was clay in texture which is considered quite fit for grape growing. The soil pH of various grape fields ranged from 7.2 to 8.8 slightly above the optimum range. The electrical conductivity values varied from 0.18 to 1.75 dS/m well below the critical concentration. The carbon content ranges from 0.23 to 1.01 kg/ha. The available nitrogen was in lower range 45 to 337.5 kg/hector. This might be due to high range of mineralization due to high temperature (dry zone) and loss of nitrogen in the form of ammonia. The soil available phosphorous content range from 15.00 to 48.9 kg/hector which was medium in range. The available potassium ranged from 115 to 592 kg/hector which were high range in all the grape fields.